PROTECTION FOR NON-FORMAL EDUCATORS IN THE SECTOR OF INTELLIGENT TECHNOLOGY IN ACCORDANCE WITH TEACHER COMPETENCY STANDARDS TO ENSURE LEGAL CERTAINTY AND JUSTICE: PROTECTION FOR NON-FORMAL EDUCATORS IN THE SECTOR OF INTELLIGENT TECHNOLOGY IN ACCORDANCE WITH TEACHER COMPETENCY STANDARDS TO ENSURE LEGAL CERTAINTY AND JUSTICE - Tjindrawan, Jully; Doradjat, Tubagus Achmad (PENA LAW: International Journal of Law, 2025)
The education sector plays a crucial role in preparing literacy skills with a new orientation and a generation ready to face the challenges of progress from the industrial revolution to the modern society era. Smart technology education currently comes from non-formal education. The government's response, through the Ministry of Primary and Secondary Education, is to issue an Academic Paper on Coding and Artificial Intelligence Learning, with the policy direction of revising the National Education System Law as an ideal concept for preparing smart technology education (robotics, coding, and artificial intelligence) into the national education system curriculum to provide legal certainty and justice for non-formal educators.